Demystifying the convergent ecological specialization of desiccation-tolerant vascular plants for water deficit - Bondi, Luiz; de Paula, Luiza F A; Rosado, Bruno H P; Porembski, Stefan (Annals of botany, 2023)
Desiccation-tolerant vascular plants (DT plants) are able to tolerate the desiccation of their vegetative tissues; as a result, two untested paradigms can be found in the literature, despite contradictions to theoretical premises and empirical findings. First, it is widely accepted that DT plants form a convergent group of specialist plants to water deficit conditions. A derived paradigm is that DT plants are placed at the extreme end of stress tolerance. Here, we tested the hypotheses that DT plants (1) are in fact convergent specialists for water deficit conditions and (2) exhibit ecological strategies related to stress tolerance, conservative resource-use and survival. We used biogeographical and functional-traits approaches to address the mentioned paradigms and assess the species' ecological strategies. For this, 27 DT plants were used and compared to 27 phylogenetically related desiccation-sensitive vascular plants (DS plants). We could not confirm either of the two hypotheses. We found that despite converging in desiccation tolerance, DT plants differ in relation to the conditions in which they occur and the ecological strategies they use to deal with water deficit. We found that some DT plants exhibit advantageous responses for higher growth and resource acquisition, which are suitable responses to cope with more productive conditions or with higher disturbance. We discuss that the ability to tolerate desiccation could compensate for a drought vulnerability promoted by higher investment in growth and bring advantages to deal with quick and pronounced variation of water, rather than to drought solely. DT plants are not only selected by drought as an environmental constraint. The alternative functional designs could promote the diversity of ecological strategies, which preclude their convergence to the same resources and conditions. Thus, DT plants are a heterogeneous group of plants in how they deal with drought, despite their desiccation tolerance ability.